Approximation structures and applications to evolution equations. (30th June 2003) - Duma, Adrian; Vladimirescu, Cristian
Abstract : We discuss various properties of the nonlinearA -proper operators as well as a generalized Leray-Schauder principle. Also, a method of approximating arbitrary continuous operators byA -proper mappings is described. We construct, via appropriate Browder-Petryshyn approximation schemes, approximative solutions for linear evolution equations in Banach spaces.